1999
DOI: 10.1159/000017365
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Dopamine D<sub>1</sub>-Like Receptors in Rat Cortical and Striatolimbic Brain Regions: An Autoradiographic Study

Abstract: Postnatal development of dopamine D1-like (D1/D5) receptors in rat caudate-putamen (CPu), nucleus accumbens (NAc), hippocampus, frontal and entorhinal cerebral cortex was assessed between postnatal days (PD) 7–60 by in vitro receptor autoradiography. Density of [3H]SCH-23390 binding to D1-like receptors increased from PD-7 to a peak at PD-28 in CPu (11-fold) and NAc (23-fold), then declined by 20–40% in both regions over PD-35–60, to adult levels. In hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 42 publications
(55 reference statements)
4
115
1
2
Order By: Relevance
“…Although all of the neurochemical "machinery" for dopaminergic transmission is present soon after birth, a number of indices of dopamine function change markedly during adolescence. Overexpression of dopamine D 1 , D 2 and D 4 receptors and subsequent decreases during adolescence have been reported in several studies [3,47,[65][66][67]. Such pruning has also been shown in postmortem studies of adolescent human brain for receptors and the dopamine transporter [44,57].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although all of the neurochemical "machinery" for dopaminergic transmission is present soon after birth, a number of indices of dopamine function change markedly during adolescence. Overexpression of dopamine D 1 , D 2 and D 4 receptors and subsequent decreases during adolescence have been reported in several studies [3,47,[65][66][67]. Such pruning has also been shown in postmortem studies of adolescent human brain for receptors and the dopamine transporter [44,57].…”
Section: Introductionmentioning
confidence: 71%
“…The mean age and range on the day of the experiment was 28 (27)(28)(29)(30) and 68 (60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77) for the PN28 and PN65 groups, respectively. Varying the frequency of electrical stimulation evokes steady-state responses at low frequencies (20 Hz) as uptake and release are balanced, and linear increases at high frequencies (60 Hz) as release overwhelms uptake.…”
Section: Resultsmentioning
confidence: 99%
“…This is one of only a limited number of investigations into the molecular underpinnings of age-related differential responses to psychostimulants, likely related to the increased plasticity of the brain during this period of extensive remodeling (Spear, 2000). Highly relevant to these studies is the literature documenting fluxes in levels of molecules identified as key mediators of cocaine's actions, including components of both the dopamine (Ehrlich et al, 1990;Tarazi et al, 1999) and neurotrophin BDNF (Ringstedt et al, 1993;Yurek et al, 1998;Costantini et al, 1999) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the prefrontal cortex (PFC)-basolateral amygdala (BLA)-nucleus accumbens (NAc) triadic circuit, responsible for reward and motivated behavior, is dynamically developing during this period, as are its monoamine afferents (Ernst et al, 2006;Ernst and Fudge, 2009). Mesolimbic DA systems, which are integral to cocaine selfadministration and locomotor sensitization (Thomas et al, 2008), undergo major reorganization during adolescence (Tarazi et al, 1999;Cao et al, 2007b;Benoit-Marand and O'Donnell, 2008;Brenhouse et al, 2008;Andersen et al, 2000) and exhibit unique sensitivity to nicotine (Azam et al, 2007). Less is known about the adolescent maturation of 5-HT systems, which have a significant role in cocaine selfadministration (Rocha et al, 1997;Rodd et al, 2005;Fletcher et al, 2002) and locomotor sensitization (Tassin, 2008).…”
Section: Introductionmentioning
confidence: 99%